PERAN BIROKRAT DESA DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT BERBASIS DIGITAL - Kusumoningtyas, Anggi Anggraeni; Sari, Inrinofita; Dwi Nurfaisal, Muhammad; Witjaksono, Ari; Lina, Nurmunafiah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This Community Service aims to analyze the role of village bureaucrats in providing digital-based services to improve the quality of public services at the village level. This activity was conducted through a socialization method involving observation and Forum Group Discussion (FGD) with 50 participants. The activity results show that implementing digitalization in Panyirapan Village has positive impacts, such as increased administrative efficiency, service transparency, and community participation. Digitalization also supports more integrated management of village assets, licensing, and social assistance programs. However, significant challenges were identified, including limited digital literacy, technological infrastructure, and resistance to change. Cybersecurity issues are a major concern, given the threat to sensitive data managed by villages.Keywords: Digitalization; Public Service; Village Bureaucrats; Digital Literacy.